2003
DOI: 10.1177/230949900301100117
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Desmoplastic Fibroma of Bone: A Case Report

Abstract: Desmoplastic fibroma is a rare benign tumour of bone. Diagnosis is not easy and is often made by excluding other tumours. Histopathological diagnosis of this tumour is also sometimes not easy. The treatment modalities for this tumour are non-uniform and often controversial. In the present case surgical options were left aside because the patient did not consent to surgery, so radiotherapy was used, with success at 3-year follow-up. This case is presented here along with a review of relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…and Nag et al . [18, 19] radiotherapy has also been shown to be a therapeutic option. Sanfiliippo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Nag et al . [18, 19] radiotherapy has also been shown to be a therapeutic option. Sanfiliippo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarily, Nag et al . [18] treated one patient with DF in the distal end of the femur with radiotherapy of 45 Gy in 25 fractions. Both authors reported deceleration of disease progression over a time period of 30 and 36 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely rare, and less than 200 cases have been reported so far 12. The most common site of affection is the jaw, followed by pelvis and long bones 34.…”
Section: Introductionmentioning
confidence: 99%
“…Также применяется лучевая и химиотерапия, которая не обладает такой эффективностью, как предыдущие методы лечения, и считается опасной для доброкачественных опухолей. Применяется при невозможности проведения последних, или при отказе пациента хирургического вмешательства [5,6]. введение десмопластическая фиброма костной тканиредкая, локально агрессивная, доброкачественная опухоль, локализующаяся в костной ткани.…”
unclassified